The Tradition of Reading Yasin Fadilah: A Functional Reception Study by the Abna Khamim Suadah Foundation in Sidoarjo - Libasut Taqwa; Aziza Nadiya Putri (Al-Muhith: Jurnal Ilmu Qur'an dan Hadits, 2026)
One of the most popular surahs practiced in Indonesian Islamic tradition is Surah Yasin. This surah has shaped reading practices and become institutionalized in Indonesian cultural tradition, one example being at the al-Qur'an Assembly of the Abna Khamim Suadah Sidoarjo Foundation. The Yasinan tradition or activity, which is held every Wednesday Kliwon after Isha' at The Oso Housing Complex, and once a month at the home of one of the congregation members, has a unique characteristic, namely that several verses are read repeatedly and interspersed with prayers and salawat. This study focuses on how the Yasinan tradition is practiced at the Abna Khamim Suadah Sidoarjo Foundation and the meaning of the Yasinan tradition for the congregation who participate in it. The participants in this activity are the men and women of the Abna Khamim Suadah Sidoarjo Foundation. The method used in this study is a qualitative method using a functional approach. In his theory, Ahmad Rafiq lists three receptions, namely Exegesis, Aesthetics, and Functionality. Meanwhile, the data collection techniques used by the researcher are observation, interviews, and documentation during the research, as well as notes from interviews with informants. The results of this study show that: (1) As a means of getting closer to God. (2) As a means of connecting with ancestors who have passed away. (3) As a means of connecting with others. (4) As a means of connecting with oneself.